A DISCOURSE ANALYSIS OF SELECTED POLITICAL SPEECHES OF PRESIDENT UHURU KENYATTA AND THE FORMER PRIME MINISTER, RAILA AMOLLO ODINGA - KIMENYE, PATRICK KIOKO (Machakos University Press, 2022)
Political discourse is one of language domain that has attracted the interests of researchers for a long while. This is because political discourse is a complex human activity that deserves critical study particularly because of its central place in the organization and management of society. This study investigates how meaning of utterances is based on the context of the speaker. The study examines the role of language in the communication and interpretation of intentions by examining selected political speeches of President Uhuru and Honourable Raila Odinga in Kenya after the handshake on 9th March 2018 as pieces of discourse with specific goals. The objectives of the current study is to: examine illocutionary acts in post handshake speeches of both President Uhuru Kenyatta and the former Prime Minister Raila Odinga, establish the linguistic features in post handshake speeches of both President Uhuru Kenyatta and the former Prime Minister Raila Odinga and to Investigate the communication intent of both President Uhuru Kenyatta and the former Prime Minister Raila Odinga post handshake speeches. The study applied the Speech Act Theory (Austin 1962 and Searle, 1969, 1979) and Fairclough‘s (1989, 1993, 1995) Critical Discourse Analysis Framework. The research design for the study was a descriptive research design that combines qualitative and quantitative methods. The target population of the study were the post handshake speeches of President Uhuru Kenyatta and former Prime Minister Raila Amollo Odinga after 9th March 2018. A sample size of 20 speeches was selected using the downsampling technique. The study was a desktop research and therefore the method of collecting data was through a checklist. Data analysis was done through quantitative and qualitative analysis. The findings of the study show that language in post handshake speeches performed the four types of illocutionary: assertives, directives, commissives, expressives and declaratives. The most dominant speeches were assertives which were (68%) of the analyzed locutions while the less dominant speech acts were expressives (9%). The analysis of linguistic features of speech acts revealed that leaders in post handshake speeches use language uniquely to construct a certain ideology. The study showed how lexical items, textual features, modality and use of rhetorical questions were used as a form of persuasive process to represent the idea of handshake and Building Bridges Initiatives. The study also found that language was used purposeful to persuade, inform, and to express the ideology of the handshake and Building Bridges Initiatives. The study recommends that the Government, policy makers, and stakeholders should always pay close attention to the political leaders‘ language use in regard to a key subject such as peace, nationhood and unity and that when sensitive ideologies are being presented to the citizens, linguists should be incorporated because they are expertise in language and they may play a role in reforms and societal perceptions. It is hoped that the study adds knowledge to the theory and practice of the scope Discourse Analysis, Pragmatics and Language and society and that it provides useful insights on educational researchers who have increasingly turned to use Critical Discourse Analysis (CDA) and Speech Act Theory to answer a set of questions about the relationship between language and society.